The correlation of different methods for the assessment of bone quality in vivo: an observational study - Oliveira, M. R. [UNESP]; Gonçalves, A. [UNESP]; Gabrielli, M. A.C. [UNESP]; de Andrade, C. R. [UNESP]; Scardueli, C. R. [UNESP]; Pereira Filho, V. A. [UNESP] (Elsevier, 2022)
Different methods for the assessment of bone quality were evaluated in this study. Sixty alveolar bone areas were investigated. Peri-apical and panoramic radiographs were obtained with an aluminium scale to assess optical density. The Lekholm and Zarb (L&Z) classification was determined through radiographic analysis and the surgeon's tactile perception. A trephine was used to obtain a bone biopsy for assessment by micro-computed tomography (micro-CT) and histomorphometry. Primary stability of the implants was assessed using insertion torque (IT) and the implant stability quotient (ISQ). The optical density on peri-apical radiographs was correlated with IT, ISQ, and micro-CT (BV, BV/BT, Tb.Th, Tb.N, BS/BV, Tb.Pf, and SMI) (rho ≤ 0.471, P ≤ 0.028). Panoramic radiography showed a correlation only with bone surface (BS) and bone surface/volume ratio (BS/TV) (rho ≤ 0.290, P ≤ 0.031). IT showed a correlation with ISQ, histometry, and micro-CT (BV, BS/TV, Tb.Th, Tb.N, BS/BV, Tb.Pf, Tb.Sp, BV/BT) (rho ≤ 0.550, P ≤ 0.022). ISQ did not show any correlation with micro-CT. The L&Z classification showed correlations with the optical density obtained in the peri-apical radiographs, histometry, osteocyte count, IT, and micro-CT (BS/BV, Tb.Sp, Tb.Pf, BV, BS/TV, Tb.Th, Tb.N) (rho ≤ 0.344, P ≤ 0.042). The L&Z bone classification and IT are reliable methods, peri-apical radiographs and ISQ are acceptable, and panoramic radiography is not a reliable method for the assessment of bone quality.
Keywords: alveolar bone atrophy; bone and bones; bone density; dental implantation; dental implants